2019
DOI: 10.1111/imj.14072
|View full text |Cite|
|
Sign up to set email alerts
|

Hepatitis C treatment for difficult to access populations: can telementoring (as distinct from telemedicine) help?

Abstract: Project ECHO® is an effective model to support primary healthcare providers treating HCV in DTAPs with similar rates of treatment uptake and SVR compared to patients in TLCs This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 20 publications
1
38
0
Order By: Relevance
“…In terms of direct patient outcome measures, three studies examined the rate of sustained virologic response among individuals treated for hepatitis C. While two articles found that SVR was similar among patients who sought care from EELM trainees and experts 16,62 -an indication of project success-another found that SVR did not differ between those seeing providers who received EELM training versus did not receive EELM training. 18 In a separate study looking at the effect of EELM on diabetes care, 65 the authors found positive results that training led to reductions in patient mean HbA1c values within practitioner panels, a result not found in a comparison group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of direct patient outcome measures, three studies examined the rate of sustained virologic response among individuals treated for hepatitis C. While two articles found that SVR was similar among patients who sought care from EELM trainees and experts 16,62 -an indication of project success-another found that SVR did not differ between those seeing providers who received EELM training versus did not receive EELM training. 18 In a separate study looking at the effect of EELM on diabetes care, 65 the authors found positive results that training led to reductions in patient mean HbA1c values within practitioner panels, a result not found in a comparison group.…”
Section: Discussionmentioning
confidence: 99%
“…Arora and colleagues 16 compared sustained virologic response (SVR) between patients at training versus trainee sites and found no difference (p > 0.05), indicating trainees (generalists) performed at a level comparable to trainers (specialists). Similarly, Mohsen and colleagues 62 compared 100 patients of providers who participated in an EELM to 100 patients who received care in a tertiary liver clinic (TLC). Initiation of direct-acting antiviral therapy was similar between groups (EELM, 78%; TLC, 81%), as was completion of treatment (EELM, 89%; TLC, 86%) and-to a lesser Figure 2 Publications by topic, year, and outcome classification.…”
Section: Patient-related Outcomesmentioning
confidence: 99%
“…Some evidence suggests that telementoring can play a useful role in this area, enabling GPs ready access to specialist support, for example via Project Echo. 14 Other potential barriers to treatment include the likelihood that clinicians are managing several competing priorities where the patient is medically unwell or has comorbid medical conditions; 4% of patients in this study had a concurrent diagnosis of hepatocellular carcinoma (4%) or died (5%) shortly after their HCV notification. This study found another reason for not prescribing antiviral treatment included that 18% of patients were HCV RNAnegative, a rate in line with published literature 22 , and in this setting treatment is not indicated.…”
Section: Discussionmentioning
confidence: 98%
“…12,13 Significant investment has been made to educate and support Australian GPs to treat HCV. A number of resources have been developed to facilitate community-based treatment, for example Project Echo, which is a telementoring, group video conferencing tool used by Liverpool Hospital to link specialist hubs and primary care providers 14 ; however much more could be done to maintain the high rate of DAA uptake in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Programs like Project ECHO (Extension for Community Healthcare Outcomes) provide tele-educating and tele-proctoring. 32 Mobile applications such as the Accreditation Council for Graduate Medical Education (ACGME) case log (https://apps.acgme.org/ connect/login), MedHub (http://www.medhub.com), and SIMPL (http://www.procedurallearning.org/simpl), that have facilitated logging of duty hours, evaluations, cases, and assessments of resident performance, illustrate some examples of how information technology can be adapted to facilitate the workflow of surgical trainees and faculty and improve engagement and wellbeing.…”
Section: Process Improvementmentioning
confidence: 99%